Diversidade de gênero na escola: documentando histórias de vida - Carvalho, Luizete Pereira de (2019)
LGBTphobia is a reality in our Brazilians schools and the lack of specific knowledge and training on the subject, makes it difficult stopping discriminatory prejudice practices. Students and teachers suffering with LGBTphobia, which causes feelings of inferiority, low self-esteem, and even school dropouts. LGBTphobia can tell us what kind of society we are developing in our schools and the school is an institution that has the function of training the citizen to start the discussion about gender, diversity and prejudice. The idea of producing a documentary came after a long time thinking about those questions, based on reports from students, teachers and other “subjects” of the real world, with the purpose of sensitizing and encouraging the exercise of reflective thinking about the subject in school units. We use the methodology of the History of Life, with the oral narrative with special attention at history of the participants, recorded in audio and video, enhancing the dialogue between the individual and sociocultural perspective. The documentary validation was made int wo stages: one with research professors from the GE-SER research group from UFRJ and the other with students from the 9th grade from Escola Estadual Mestre Hiram. Students and researchers watched the documentary and answered the evaluation questionnaires. Our intent as a result with this final product turns into a educational tool that encourages dialogue and show to our students a new way of seeing the world.